(untitled) (Research, Society and Development, 2022)
Objective: To temporally and spatially analyze hospitalizations for abortion in Brazil and regions from 2012 to 2021. Methodology: Ecological study, with data from the Hospital Information System (SIH/DATASUS) on hospitalization for abortion in Brazil and regions from 2012 to 2021. Hospital admission rates (HIT) and Spatial Empirical Bayesian Rates (TBEE) were calculated. The TIH were used for temporal trend analysis performed through JoinPoint. The TBEE were used for the spatial model, through the Moran Index (MI). Results: The time trend of abortion by “other pregnancies that end in abortion” was decreasing with Annual Percentage Variation – APV of -0.7%, spontaneous open was also decreasing with -3.9% and abortion for medical reasons was growth rate of 2.5% per year. The North was the only region that showed an increase in abortion due to other pregnancies, with 2.6% per year, while for medical reasons the increase was 8.9%. The Southeast region showed a predominance of reduction with -2.7% (other pregnancies) and -4.5% (spontaneous) and the South with -2.9% (spontaneous) and -3.9% (medical reasons). In the spatial analysis, an inverse autocorrelation was identified between HDI and RPC and hospitalization TBEE. The South and Southeast regions showed a predominance of municipalities with low rates and high HDI and RPC, while the North and Northeast showed high rates with low HDI and RPC. Conclusion: The time trend was diverse. The growth was observed in abortion for medical reasons, mainly in the North, Northeast and Midwest. The Southeast and South showed a reduction. There was an inverse correlation between the HDI and RPC of the municipalities with the TBEE.